High temperature corrosion behaviour of austenitic stainless steel with CaCO3 and MgCO3 Deposit - Habsah Md Ishak
The objectives of the research are to study the high temperature corrosion behavior of the austenitic stainless steels in carbonate salts, to investigate the rate of oxidation at high temperature from 850 - 10000C, to determine the microstructural morphology of scales on the surfaces of corroded austenitic stainless steel by using scanning electron microscope (SEM) and to determine elements and chemical compounds of scale formed on austenitic stainless steel by using energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction technique (XRD).